Motivação, suporte parental e satisfação: estudo da trajetória esportiva de atletas de beisebol - Mizoguchi, Marcus Vinícius (2012)
The aim of this study was to investigate the process of development of motivation, parenting support and satisfaction of Brazilian baseball athletes career. Population used was 227 males (23,82±41) of 17 baseball' teams of season 2011/2012. The instruments used were: identification sheet, Sport Motivation Scale- SMS, parenting style perception test- EMBU, Athletes Satisfaction Questionnaire- ASQ and semi structured interview. For data collection, it was scheduled the days and locals to collect the psychometric tests with each team and the semi-structured interviews with the champion' team of 2012. The analysis of the quantitative data used were descriptive statistics, Mauchly's test of sphericity, repeated measure ANOVA with confidence interval adjustment of Bonferroni, independent sample t test and Pearson correlation. The level of significance was set at 5%. For qualitative data, it was used content analysis of categorical type. The results showed: baseball' athletes had high levels of intrinsic motivation for the sport; parents demonstrated parenting style of emotional support in their children' perception, and mothers presented more emotional support and overprotection than fathers; levels of athletes satisfaction were high, showing more satisfaction in personal dedication, personal treatment and team task contribution; support emotional of father provides more extrinsic motivation for their children, while some behaviors of rejection and overprotection motive intrinsically the athletes; individuals who were intrinsically motivated are more likely to show satisfaction behaviors in sport context; it was found that activities realized by baseball athletes were properly performed, starting with several deliberate play until specialize in one sport, working deliberate practices; autonomy and athlete competence increased over the athlete career, moving from external to internal influence; parents, friends, coach and club have demonstrated to be an important social agents in the career development of the individual. Baseball athletes have shown appropriated sportive development process, being self-determined, parenting support with satisfaction at different stages of sport career.